Whole genome sequencing of 91 multiplex schizophrenia families reveals increased burden of rare, exonic copy number variation in schizophrenia probands and genetic heterogeneity - Khan, F.; Melton, Phillip; McCarthy, N.; Morar, B.; Blangero, J.; Moses, Eric; Jablensky, A. (2018)
The importance of genomic copy number variants (CNVs) has long been recognized in the etiology of neurodevelopmental diseases. We report here the results from the CNV analysis of whole-genome sequences from 91 multiplex schizophrenia families. Employing four algorithms (CNVnator, Cn.mops, DELLY and LUMPY) to identify CNVs, we find 1231 rare deletions and 287 rare duplications in 300 individuals (77 with schizophrenia (SZ), 32 with schizoaffective disorder (SAD), 82 with another neuropsychiatric diagnosis and 109 unaffected). The size of the CNVs ranges from a few hundred base-pairs to about 1.3 Mb. The total burden of CNVs does not differ significantly between affected (SZ and SAD) and unaffected individuals. Parent-to-child transmission rate for rare CNVs affecting exonic regions is significantly higher for affected (SZ and SAD) probands as compared to their siblings, but rates for all CNVs is not. We observe heterogeneity between families in terms of genes involved in CNVs, and find several CNVs involving genes previously implicated in either schizophrenia or other neuropsychiatric disorders.